2008
DOI: 10.1258/ijsa.2008.008127
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections among brothel-based sex workers in Tel-Aviv area, Israel: high prevalence of pharyngeal gonorrhoea

Abstract: Sex workers play a major role in spreading sexually transmitted infections (STIs). We studied the prevalence rates and risk factors for STIs among 300 brothel-based sex workers in Tel-Aviv. Throat swabs were cultured for Neisseria gonorrhoeae, urine samples were tested by polymerase chain reaction (PCR) for Chlamydia trachomatis and N. gonorrhoeae, and sera were tested for syphilis, human immunodeficiency virus (HIV) and type 2 herpes simplex virus (HSV) antibodies. N. gonorrhoeae was cultured from throat samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…In Tel-Aviv, a study of brothel-based female sex workers (90% of whom were from the former Soviet Union) showed high prevalence (9%) of pharyngeal gonorrhea (39). While vaginal condom use was almost universal, only two thirds of female sex workers practiced condom use with oral sex, and the result was an epidemic of gonorrhea arising from oral sex.…”
Section: Sexually Transmissible Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tel-Aviv, a study of brothel-based female sex workers (90% of whom were from the former Soviet Union) showed high prevalence (9%) of pharyngeal gonorrhea (39). While vaginal condom use was almost universal, only two thirds of female sex workers practiced condom use with oral sex, and the result was an epidemic of gonorrhea arising from oral sex.…”
Section: Sexually Transmissible Infectionsmentioning
confidence: 99%
“…While vaginal condom use was almost universal, only two thirds of female sex workers practiced condom use with oral sex, and the result was an epidemic of gonorrhea arising from oral sex. The fact that HIV is rarely transmitted by oral sex appears to have been inaccurately generalized to bacterial STI (39).…”
Section: Sexually Transmissible Infectionsmentioning
confidence: 99%
“…1 -3 A recent study performed in Tel-Aviv district found that 9% of all commercial sex workers (CSWs) tested were infected with pharyngeal gonorrhoea. 3 Due to the asymptomatic nature of pharyngeal NG infection, the patient may be unaware of his/her risk for onward transmission to other sexual partners. The limited public awareness regarding the risks involved in OS and the relative lower intimacy involved in OS compared with vaginal or anal intercourse may promote fellatio.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the female CSW population in Israel has been augmented by immigrants, mainly originating from eastern European countries. 3,12,13 In the face of increasing NG incidence and the changing composition of CSWs in Tel-Aviv district, we conducted a study among patients diagnosed with NG to assess behavioural risks and to identify the source of infection. The findings of this study can be used to guide behavioural interventions to decrease STI morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiological data show a decreased trend in gonorrhea incidence as a whole, in some countries, the incidence is increasing, especially in specific population groups (adolescents, men who have sex with men, or sex workers) or specific venues (brothels) (2)(3)(4)(5). The pathogen responsible for this disease is Neisseria gonorrhoeae.…”
mentioning
confidence: 99%